Active restoration efforts in the Central Mexican Pacific as a strategy for coral reef recovery - Martínez-Castillo, Violeta; Rodríguez-Troncoso, Alma Paola; Tortolero-Langarica, José de Jesús Adolfo; Cupul-Magaña, Amílcar Leví (Revista de Biología Tropical, 2023)
Introduction: The 1997-98 El Niño event caused massive coral bleaching and mortality in the Central Mexican Pacific (CMP). Punta de Mita alone used to harbor more than 30 % of the coral coverage in this region, with a mono-specific Pocillopora coverage. The 1997-1998 ENSO event caused massive coral mortality reducing live coral coverage to < 5 %. Despite being considered a coral region unlikely to recover, recent restoration efforts have been implemented to rehabilitate the coral community. Objective: To assess coral recovery by analyzing the coral growth and survival rates of branching Pocillopora species at Punta de Mita. Methods: Healthy coral fragments of opportunity were re-attached to the natural substrata using zip ties and measured considering their growth in terms of maximum length and width (cm) to determine their annual extension rates. Results: After 50 weeks, corals duplicated their size, with a mean growth of ~ 4 cm year-1. After 100 weeks (2 years), corals triplicated their size, increasing on average 8–9 cm in each diameter. Conclusions: Successful coral reef restoration activities in the Central Mexican Pacific are the result of Pocillopora’s physiological processes, such as fast growth rates, and recent life-history traits, like the ability to cope with thermal anomalies, which enable them to thrive in a dynamic region severely affected by natural and anthropogenic perturbations. Indeed, a region considered unlikely to recover has regained its live coral cover from < 5 % in 1998 up to 15 % in 20 years. This demonstrates the importance of assisting natural coral recovery with restoration efforts, especially in coral locations that, despite environmental perturbations, have proven to be resilient and may become coral refugia areas under the current climate change scenario.